ANALISIS MEKANISME PEMUNGUTAN, PELAPORAN, DAN EFEKTIVITAS PAJAK PENGHASILAN PASAL 22 DI INDONESIA - Ayu Hani Marsani Tanjung; Fadillah Syafitri; Zahir Muhammad Fadhilah Harahap (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Income Tax Article 22 (PPh Article 22) is a tax imposed on certain activities, such as imports, sales, and procurement by government treasurers or certain entities. This tax functions as a preliminary levy on income earned by taxpayers. The purpose of this descriptive qualitative research is to determine the process of calculating, withholding, depositing, and reporting Income Tax Article 22, as well as the success rate of its implementation in supporting state revenue. As a result, the average ITA 22 is usually 1.5% of the tax base, and the payment is made on time. However, periodic reporting of Income Tax Article 22 returns is quite difficult, especially for government treasurers who According to the results, Income Tax Article 22 is usually 1.5% of the tax base on average, and payments are made on time. However, there are difficulties to report the Surat Pemberitahuan (SPT) for ITA 22, especially for government treasurers who believe that the e-billing system is sufficient to report. The study suggests improving knowledge about its reporting to support tax transparency and compliance.